New user? Sign up

Existing user? Sign in

I need help for the problem shown above.

Note by Pranjal Rs 4 years, 6 months ago

Sort by:

Multiply numerator and denominator by 5^(1/16) - 1, and apply a^2 - b^2 = (a-b)(a+b) a couple of times, you get

x = 4(5^(1/16 - 1)/(5 - 1) = 5^(1/16) - 1

x + 1 = 5^(1/16)

(x + 1)^48 = 5^(48/16) = 5^3 = 125

Answer is (B)

Log in to reply

Hey!! Thank you very very much friend.Needed it badly. Regards Pranjal

very good so intersting

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestMultiply numerator and denominator by 5^(1/16) - 1, and apply a^2 - b^2 = (a-b)(a+b) a couple of times, you get

x = 4(5^(1/16 - 1)/(5 - 1) = 5^(1/16) - 1

x + 1 = 5^(1/16)

(x + 1)^48 = 5^(48/16) = 5^3 = 125

Answer is (B)

Log in to reply

Hey!! Thank you very very much friend.Needed it badly. Regards Pranjal

Log in to reply

very good so intersting

Log in to reply